Green Recycling Process for Polyurethane Foams by a Chem‐Biotech Approach. Issue 19 (5th March 2021) - Magnin, Audrey; Entzmann, Lisa; Bazin, Alfred; Pollet, Eric; Avérous, Luc
Abstract: Polyurethanes (PUs) are highly resistant materials used for building insulation or automotive seats. The polyurethane end‐of‐life issue must be addressed by the development of efficient recycling techniques. Since conventional recycling processes are not suitable for thermosets, waste management of PU foam is particularly questioning. By coupling biological and chemical processes, this study aimed at developing a green recycling pathway for PU foam using enzymes for depolymerization. For instance, enzymatic degradation of a PU foam synthesized with polycaprolactone and toluene diisocyanate led to a weight loss of 25 % after 24 h of incubation. The corresponding degradation products were recovered and identified as 6‐hydroxycaproic acid and a short acid‐terminated diurethane. An organometallic‐catalyzed synthesis of second‐generation polymers from these building blocks was carried out. A polymer with a high average molar mass of 74000 ( M w ) was obtained by mixing 50 % of recycled building blocks and 50 % of neat 6‐hydroxycaproic acid. A poly(ester urethane) was synthesized without the use of toxic and decried polyisocyanates. It is the first time that a study offers the vision of a recycling loop starting from PU wastes and finishing with a second‐generation polymer in a full circular approach. Abstract : Bio‐recycling of poly(ester urethane) : A poly(ester urethane) foam is depolymerized using the Candida Antarctica lipase B. Two types of degradation products are identified. A thermoplastic poly(ester urethane) is obtained by polycondensation from these degradation products, highlighting the bio‐recyclability of this type of polymer.